Non-subsumptive memory and narrative empathy - Meretoja Hanna (SAGE PUBLICATIONS INC, 2025)
This article shows the relevance of a model of non-subsumptive understanding for theorising memory as a mode of sense-making that can contribute to understanding the other in ethically sustainable ways. It develops a theory of non-subsumptive memory and narrative empathy. While understanding is often seen as a form of appropriation, assimilation, and subsumption of the singular under the general, a hermeneutic approach suggests that there are also non-subsumptive, non-appropriative, dialogical forms of understanding. In dialogue with Jenny Erpenbeck's novel Gehen, ging, gegangen (Go, Went, Gone), the article argues that cultural memorial forms, as (narrative) models of sense-making, tend to be productive when they adapt and change as they are applied to new situations and harmful when they subsume new experiences under fixed meaning templates. The article envisages memory as a resource for learning and other-oriented empathy in processes of dialogical understanding.